Frontotemporal dementia - behavioral variant as a differential diagnosis of primary psychiatric disorders - Cruzado, Lizardo (2021)
Frontotemporal dementia (FTD) was described by Arnold Pick more than a century ago. It is a type of dementia in which multiple clinical manifestations of behavior and language predominat. The first and most frequent subtype, called behavioral variant frontotemporal dementia (bvFTD), which, due to a variety of clinical presentations, can be confused with primary psychiatric conditions such as depression, bipolar disorder, obsessive-compulsive disorder, late-onset psychosis, impulse control disorders, and other pathologies. Recently, an important and promising stream of clinical, neurobiological, and genetic research offers fascinating insights into this disorder which, thus, becomes a paradigm of the intricate relationships between neurology and psychiatry. This review examines recent bibliography on bvFTD , with emphasis on aspects of its differential diagnosis.